Religious Engagement within Refugee Resettlement in Canada: Lessons to Learn - Muhammad Izzul Haq (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
In recent years, Canada has become a global leader in refugees and the top world leader in refugee resettlement. Direct participation by civil society, mainly dominated by the religious congregation and faith-based organizations in resettlement, has been the hallmark of Canada's private sponsorship program and a significant element in its success.  This paper explores the evidence base of existing literature covering religious engagement within Canada's umbrella of refugee resettlement. Religious engagement is exemplified by the involvement of religious groups, congregations or communities in refugee resettlement which defines and shapes this policy, particularly in the private refugee sponsorship program.  Despite challenges shadowing the process, religious engagement contributes to more outcomes given its potential social capital. It is predicted that religious groups will continue to be leading actors within Canada’s resettlement programs.